Aesthetics and Musical Subcultures Today: A Conversation with Simon Reynolds - Marino, Stefano; Mugnaini, Giovanni (Scenari, 2024)
In this interview Stefano Marino and Giovanni Mugnaini posed some questions to a great expert of popular music at an international level, Simon Reynolds, who offered extensive and detailed replies. The result is a dense conversation that summarizes all the main themes animating this issue of “Scenari”: the relationship between philosophy and popular music; the intersection between technology (AI) and popular music; the Adornian legacy in the philosophy of music and in musicology; the heuristic validity of the concept of subculture. Reynolds’ observations allow for a more detailed reconstruction of the relationship between philosophy, understood as cultural production and theory (not merely as an academic discipline) and popular music. Indeed, numerous precedents of “philosophical” interest in the popular are cited, offering a historical perspective on this relationship. This approach helps evaluate the concepts and theories underpinning it.